2006
DOI: 10.1002/star.200600525
|View full text |Cite
|
Sign up to set email alerts
|

Gel and Pasting Behaviour of Fenugreek‐Wheat Starch and Fenugreek – Wheat Flour Combinations

Abstract: The influence of fenugreek material on starch and flour rheological characteristics was determined. Ground fenugreek grain material, and a purified fenugreek extract (Fenulife®) were used as replacement or as addition to flour or starch. Evaluation of the pasting properties of starch and flour fenugreek mixtures illustrated that fenugreek addition increased the peak and final viscosity of the mixtures in relation to the level of fenugreek addition used. The ground fenugreek seeds yielded a lower response than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
3
14
1
Order By: Relevance
“…This neutralization results in intramolecular electrostatic repulsion promoting a network of FG and PS that inhibits the expansion and swelling of the potato starch granules. These results are in agreement with those reported by Brennan et al 23 . Addition of NaCl, however, did not produce an effect on peak viscosity of xanthan gum-rice starch 20 .…”
Section: Resultssupporting
confidence: 94%
“…This neutralization results in intramolecular electrostatic repulsion promoting a network of FG and PS that inhibits the expansion and swelling of the potato starch granules. These results are in agreement with those reported by Brennan et al 23 . Addition of NaCl, however, did not produce an effect on peak viscosity of xanthan gum-rice starch 20 .…”
Section: Resultssupporting
confidence: 94%
“…This starch granule swelling and rising up of the linseed gum concentration resulted in the improved viscous nature of gels that alluded the thickening ability of gum (Achayuthakan & Suphantharika 2008). Brennan et al (2006) also observed higher PV with increasing concentrations of fenugreek gum. It is suggested that the blends with high PV might be used for bread and other baked products for the better texture (Inglett et al 2013).…”
Section: Resultsmentioning
confidence: 87%
“…NSPs have been added to starch-based food systems to modify or control rheological and textural properties and improve the stability of food products (Rojas et al, 1999;Brennan et al, 2008;Techawipharat et al, 2008;Zhou et al, 2008). Brennan et al (2006) found that the viscosity of wheat flour pastes increased with addition of fenugreek material. The gel texture of wheat flour incorporated with fenugreek had greater hardness, although the gels became softer with higher levels of fenugreek material used.…”
Section: Introductionmentioning
confidence: 99%